Respon Pertumbuhan dan Hasil Tanaman Kedelai (Glycine max L.) Varietas Nuansa Sanggabuana Terhadap Pemberian Kombinasi Pupuk Organik Cair Keong Mas dan NPK - Andina Nursyahfika; Fawzy Muhammad; Winda Rianti (JURNAL AGROPLASMA, 2026)
Soybean production in Indonesia tends to continue to decline due to land degradation, so a combination of NPK fertilizer and golden snail liquid organic fertilizer is needed to increase soil and soybean plant productivity. Aim of this research is to obtain the highest combination of golden snail liquid organic fertilizer and NPK for the growth of soybean plants. The research was carried out in Pasirawi, Rawamerta, Karawang from June to August 2023. Research method used was an experimental method, with a single factor randomized block design (RAK), consisting of 10 treatments and 3 replications. The combination treatment of NPK fertilizer and golden snail liquid organic fertilizer consisted of A (0ml/L POC + 0kg/ha NPK); B (300ml/L POC + 100kg/ha NPK); C (400ml/L POC + 100kg/ha NPK); D (500ml/L POC + 100kg/ha NPK); E (300ml/L POC + 200kg/ha NPK); F (400ml/L POC + 200kg/ha NPK); G (500ml/L POC + 300kg/ha NPK); H (300ml/L POC + 300kg/ha NPK); I (400ml/L POC + 300kg/ha NPK); J (500ml/L POC + 300kg/ha NPK). Observation data were analyzed using variance analysis and further tested with the Duncan Multiple Range Test (DMRT) at the 5% level. Results showed that Treatment I (400ml/L POC + 300kg/ha NPK) gave the best results for plant heights of 2 wp (18,110 cm) & 4 mst (38,732 cm), number of leaves 2 mst (8,389 pieces) & 4 wp (24,457 pieces), weight wet pods (810 g), dry pod weight (419.107 g), & 100 seed weight (104.104 g). Keywords: soybeans, NPK, gold snail liquid organic fertilizer, nuansa sanggabuana